(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Passive dynamic walking is an essential development for the biped robots. So the focus of our work is a systematic analysis of the passive walk of a planar biped robot on an inclined slope. The dynamics of passive biped robot is only caused of gravity. The biped robot with two point masses at kneeless legs and a third point mass at the hip-joint is kinematically equivalent to a double pendulum. In this paper, we represent a general method for developing the equations of motion and impact equations for the study of multi-body systems, as in bipedal models. The solution of this system depends on the initial conditions. But it is difficult to find the proper initial conditions for which the system has solutions, in other words, the initial conditions for which the robot can walk. In this paper, we describe the cell mapping method which able to compute the feasible initial conditions for which the biped robot can move forward on the inclined ramp. The results of this method described the region of feasible initial conditions is small and bounded. Moreover, the results of cell mapping method give the fixed of Poincare map which explains the symmetric gait cycle of the robot and describe the orientation of legs of robot.